LEGAL REVIEW OF WOMEN'S REPRODUCTIVE HEALTH RIGHTS IN LOVE RELATIONSHIPS WITHOUT MARRIAGE - Nency Ayu Lianawati; Aris Prio Agus Santoso; Peter Guntara (Law Studies and Justice Journal (LAJU), 2025)
The right to reproductive health is a human right guaranteed by various regulations in Indonesia. However, the implementation of this right often faces obstacles, particularly for women in unmarried relationships. This group often experiences limited access to services, discrimination, and social stigma, which worsens physical and psychological conditions. Therefore, this research is crucial to examine the alignment between legal guarantees and practices in the field. This research uses the following method:normative juridical with a statutory regulatory approach. The analysis focuses on Law No. 17 of 2023 concerning Health, Law No. 4 of 2024 on the Well-Being of Mothers and Children, PP No. 61 of 2014 concerning Reproductive Health, as well as Minister of Health Regulation No. 2 of 2025 concerning the Implementation of Reproductive Health Efforts. The study results show that women, including those in unmarried relationships, are legally entitled to quality, safe, and discrimination-free reproductive health services. However, respondents have not fully accessed formal health services, including education, counseling, and medical support. Support is primarily obtained from family and religious institutions. The biggest barriers lie in social stigma and discrimination, which negatively impact respondents' mental and social health.